(untitled) (Medico Legal Update, 2020)
Background/Objectives: The aim of this study was to investigate the effect of action observation training combined with intrinsic muscle stimulation intervention on the function of upper extremity in patients with stroke. Method/Statistical Analysis: Twenty-two stroke patients were prospectively randomized to action observation training with intrinsic muscle stimulation group (N = 11) or action observation (N = 11). The upper limb of motor function and sensory function were evaluated before intervention, and intervention was performed 3 times a week, 40 minutes, 4 weeks, and the same evaluation was performed after intervention. The outcome measure was used by manual function test and sensory test. Findings: The results of this study showed that there was a significant difference in the test within the group. There was statistically significant difference in manual function test and sensory test in the inter body test. Improvements/Applications: This study demonstrated that action observation training combined with intrinsic muscle stimulation significantly improves the function of patients with stroke.